2013
DOI: 10.4103/0970-9290.127607
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal fingerprints: A key to early diagnosis of caries

Abstract: The research confirms the impact of hormones on human perception of taste and dietary preferences, which in turn influence their caries index and could also extend way beyond it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…In the present study, 81.7% of males and 79.6% of the females had low 2D:4D ratio, consistent with a study by Verma et al, 5 who reported that 80% of the sweet likers had low 2D:4D ratio.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, 81.7% of males and 79.6% of the females had low 2D:4D ratio, consistent with a study by Verma et al, 5 who reported that 80% of the sweet likers had low 2D:4D ratio.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study non-tasters and tasters of PROP were 57.4% and 42.6%, respectively, consistent with studies by Verma et al 5 Pidamale et al, 4 and contradicting with the results reported by Rupesh and Nayak, 18 where the non-tasters were found to be 19.5%. In our study, the were more numerous female tasters (54.3%) compared to the males (45%), consistent with the findings of Rupesh and Nayak, 18 which was attributed to the fact that increased number of fungiform papillae enhance the sensitivity to bitter taste as reported by Shahbake et al 19 and Delwiche et al 20 Among the dietary preferences, the majority of the subjects who were dubbed as non-tasters were interpreted as sweet likers and studies also suggest that there are difference in food preferences between tasters and non-tasters, with Pidamale et al 4 and Verma et al 9 reporting that non tasters were sweet likers.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…(2016) 8 on 500 children with the age range of 6 and 14 years from both sexes to evaluate the association between genetic taste sensitivity, dietary preferences, and salivary flow rate for identification of individuals at higher risk of developing dental caries proposed a positive relation between low 2D:4D ratio, nontasters, sweet likers, and high caries index with a highly significant statistical difference. Verma P et al(2013) 9 conducted a study to determine the correlation between 2D:4D ratio and caries riskin 250 children with age ranging from 6 to 16 yearsusing PROP (6-n-propylthiouracil) sensitivity test. They reported a positive correlation between low 2D:4D ratio, i.e.…”
Section: Resultsmentioning
confidence: 99%